2011
DOI: 10.1063/1.3607480
|View full text |Cite
|
Sign up to set email alerts
|

Bias current dependence of spin accumulation signals in a silicon channel detected by a Schottky tunnel contact

Abstract: We study the electrical detection of spin accumulation at a ferromagnet-silicon interface, which can be verified by measuring a Hanle effect in three-terminal lateral devices. The device structures used consist of a semiconducting Si channel and a Schottky tunnel contact. In a low currentbias region, the Hanle-effect curves are observed only under forward bias conditions. This can be considered that the electrical detectability at the forward-biased contact is higher than that at the reverse-biased contact. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 19 publications
7
88
0
Order By: Relevance
“…Because the spin diffusion length of this system is unknown, we resort to a three-terminal measurement geometry with only one ferromagnetic tunnel contact and focus on spin injection [25], essential for future lateral spin valves based on this system. This 3-T geometry has recently been employed to probe the spin-injection efficiency in semiconductor channels [6,[26][27][28][29][30][31][32]. Spin injection is then detected through a correlated change of the spin splitting and voltage at the interface between the tunnel contact and the channel.…”
Section: Motivationmentioning
confidence: 99%
“…Because the spin diffusion length of this system is unknown, we resort to a three-terminal measurement geometry with only one ferromagnetic tunnel contact and focus on spin injection [25], essential for future lateral spin valves based on this system. This 3-T geometry has recently been employed to probe the spin-injection efficiency in semiconductor channels [6,[26][27][28][29][30][31][32]. Spin injection is then detected through a correlated change of the spin splitting and voltage at the interface between the tunnel contact and the channel.…”
Section: Motivationmentioning
confidence: 99%
“…Hereafter, we focus on the effect of the magnetic domain structure in the FM contact used on the spin accumulation signals as one of the possible origins of the discrepancies between theories and experiments, because variously-sized FM contacts which can give rise to various magnetic domain structures have so far been utilized for the 3T measurements in the previous studies [1][2][3][4][5][6][7][8][9][10][11]. For the spin valve devices with multiple FM contacts which can detect the spin accumulation after intermixing of whole injected spins, it has been revealed that the magnetic domain structure of the spin injector strongly affects the spin accumulation signals [13].…”
mentioning
confidence: 99%
“…The CoFe/Si(111) interface was atomically flat and was utilized for the three-terminal lateral device [4,7], as shown in Fig. 1(a).…”
mentioning
confidence: 99%
See 2 more Smart Citations